2020
DOI: 10.3390/foods9070907
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Selected Product and Process Parameters on Microstructure, Rheological, and Textural Properties of 3D Printed Cookies

Abstract: One of the major advantages of 3D food printing is the customizability in terms of structure, design, and nutritional content. However, printability of the ingredients and the quality of the 3D printed food products are dependent on several product and printing parameters. In this study, nutrient dense cookies were developed with underutilized ingredients including jackfruit seed powder and finger millet powder as base materials using 3D food printing. The hardness, rheological behavior, and microstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…G’ and G” increased with high levels of GBF addition in wheat flour, indicating that an addition GBF improved the dough viscoelasticity. The tan δ lower than 1 for all dough samples showed a solid-like behavior of the dough samples [ 70 ]. Tan δ presented higher values for dough samples with GBF addition, which indicated the decreased in the ratio of elastic structure.…”
Section: Discussionmentioning
confidence: 99%
“…G’ and G” increased with high levels of GBF addition in wheat flour, indicating that an addition GBF improved the dough viscoelasticity. The tan δ lower than 1 for all dough samples showed a solid-like behavior of the dough samples [ 70 ]. Tan δ presented higher values for dough samples with GBF addition, which indicated the decreased in the ratio of elastic structure.…”
Section: Discussionmentioning
confidence: 99%
“…This theory is supported by the higher porosity of the milk-based samples as determined with X-ray tomography ( Table 3 ) and might be one reason why the addition of rye flour improved the baking stability of the milk-based system. A benefit of 3D printing is its ability to create low fill density and large surface area products in which water evaporation during baking is more effective than in more dense conventional products [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, a lower printing temperature had a prominent effect on reducing undesirable colour change while improving printing precision, even though the dough continued to be stored at ambient conditions. A lower temperature assures more defined printing and consistency of the dough, while at higher temperature, the 3D-printed cookie dough has lower strength and rigidity but also higher complex viscosity (Varghese et al, 2020). Rando and Ramaioli (2021) showed that the post-deposition material temperature is mainly affected by ambient air, build plate temperature and printing velocity.…”
Section: Influence Of Flour Type Dough Ph and Printing Temperature On Enzymatic Browning And Printing Performancementioning
confidence: 99%